The Multidisciplinary Team Conference's Decision on M-Staging in Patients with Gastric- and Gastroesophageal Cancer is not Accurate without Staging Laparoscopy. (June 2016) - Strandby, R. B.; Svendsen, L. B.; Fallentin, E.; Egeland, C.; Achiam, M. P.
Background: The implementation of the multidisciplinary team conference has been shown to improve treatment outcome for patients with gastric- and gastroesophageal cancer. Likewise, the staging laparoscopy has increased the detection of patients with disseminated disease, that is, patients who do not benefit from a surgical resection. The aim of this study was to compare the multidisciplinary team conference's decision in respect of M-staging with the findings of the following staging laparoscopy. Methods: Patients considered operable and resectable within the multidisciplinary team conference in the period 2010–2012 were retrospectively reviewed. Patient data were retrieved by searching for specific diagnosis and operation codes in the in-house system. The inclusion criteria were as follows: biopsy-verified cancer of the esophagus, gastroesophageal junction or stomach, and no suspicion of peritoneal carcinomatosis or liver metastases on multidisciplinary team conference before staging laparoscopy. Furthermore, an evaluation with staging laparoscopy was required. Results: In total, 222 patients met the inclusion criteria. Most cancers were located in the gastroesophageal junction, n  = 171 (77.0%), and most common with adenocarcinoma histology, n  = 196 (88.3%). The staging laparoscopy was M1-positive for peritoneal carcinomatosis in eight patients (16.7%) with gastric cancer versus nine patients (5.3%) with gastroesophageal junction cancer. Furthermore, liver metastases were evident in zero patients (0.0%) and four patients (2.3%) with gastric- and gastroesophageal junction cancer, respectively. The staging laparoscopy findings regarding peritoneal carcinomatosis were significantly different between gastric- and gastroesophageal junction cancers, p  = 0.01. No significant differences were found regarding T-/N-stage or histological tumor characteristics between the positive- and negative-staging laparoscopy group. Conclusion: The M-staging of the multidisciplinary team conference without staging laparoscopy lacks accuracy concerning peritoneal carcinomatosis. Staging laparoscopy remains an essential part of the preoperative detection of disseminated disease in patients with gastric- and gastroesophageal cancer.